A sensitive hydrogen peroxide sensor based on a three-dimensional N-doped carbon nanotube-hemin modified electrode. Issue 19 (7th October 2015) - Zhang, Man; Huang, Zhenzhong; Zhou, Gangyong; Zhu, Li; Feng, Yan; Lin, Ting; Hou, Haoqing; Guo, Qiaohui
<x xml:space="preserve">Abstract</x> Uniform N-doped CNTs are bonded onto electrospun carbon nanofibers, resulting in a flexible 3D composite with applications in H2O2 biosensing.